STUDENTS’ PERCEPTION OF ENGLISH LANGUAGE LEARNING THROUGH TIKTOK SOCIAL MEDIA - Mutmainnah; Jusriati; Nasriandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to explore students’ perceptions of using TikTok as a medium for learning English. As the use of social media in education continues to grow, TikTok has become one of the platforms frequently utilized by students to access learning materials that are engaging, interactive, and easy to understand. Using a descriptive qualitative approach, data were collected through semi-structured interviews with five English Language Education students at Muhammadiyah University of Palopo who actively use TikTok for learning. The findings reveal that students respond positively to TikTok as a learning tool. They perceive features such as Duet, Stitch, subtitles, and trend-based videos as helpful in improving vocabulary, pronunciation, listening skills, and speaking confidence. TikTok is also considered capable of boosting learning motivation due to its appealing content, easy accessibility, and alignment with the learning preferences of young users. Nevertheless, students still encounter several challenges, including inaccurate information, distractions from non-educational content, limited interaction, and short video duration that often lacks in-depth explanations. Despite these limitations, TikTok is viewed as an effective supplementary medium when used selectively and combined with formal instruction. Overall, the study concludes that TikTok holds strong potential as a creative and flexible additional learning tool that can enhance students’ English language proficiency.